The openness growth monitoring model (OGM-Model): A note for JPM readers - Ruiz Estrada, Mario Arturo; Yap, S.F. (Elsevier, 2010)
This short communication is interested to give more details about how the Openness Growth Monitoring Model (OGM-Model) works to the JPM readers. The main idea is to extend certain points from the original paper entitled ``The Openness Growth Monitoring Model'' that was published in the Journal of Policy Modeling in the year 2006. (C) 2010 Society for Policy Modeling. Published by Elsevier Inc. All rights reserved.